Aplicación de contabilidad comercial en establecimiento: 002 “Plastimavic” de la empresa Sodom S.A., ubicado en el cantón El Triunfo, provincia del Guayas; periodo: septiembre 2014 - Carcelén Ruíz, Mery Mercy (2015)
The execution of this so-called investigative work: "commercial accounting application in establishment: 002"PLASTIMAVIC"of the company SODOM S.A., located in the CANTON EL TRIUNFO, province of GUAYAS;" PERIOD: SEPTEMBER2014 ", justification in the first place was to comply with one of the requirements of the academic of the University National regime of Loja prior to graduation and degree of engineer in accounting and auditing. CPA., and second provide the company with the knowledge acquired concerning the commercial accounting. The goals were given compliance in its entirety through the application of the same commercial accounts that started with the preparation of the chart of accounts and detail in the respective accounts Manual, then once verified documentation existing in the company support developed the inventory of assets, rights and obligations of the local and was determined the heritage; values that are passed to the State of initial situation, as for the control of goods applied the weighted average method for the control of inputs and outputs of the articles and finally continued registration of the transactions in the journal book, Mayorización, Trial Balance, internal documents as worksheet, book shopping and sales, role of payments, depreciation of property, plant and equipment registration of accounts consumption, etc., to determine the financial statements. In conclusion this accounting proposal allowed to deliver to the owner of the company a real vision of the correct way to operate that any commercial entity must apply in order to maintain financial control of his activities directing its objectives and goals better and facilitate sound decision-making at any time